Differential analysis of hash functions and block ciphers: generalized approach - Кудін, Антон Михайлович; Коваленко, Богдан Анатолійович (Ukrainian Scientific Journal of Information Security, 2015)
Differential analysis approaches are powerful block cipher analysis methods. Similar methods are used for hash function analysis. This paper generalizes differential analysis of unbalanced Feistel scheme based hash functions and Feistel block ciphers. Obtained results demonstrate, despite on some similarity of differential analysis for cipher and hash functions, they have crucial differences, so the same security parameters may belong to different resistances to differential analysis of cipher and hash functions. These results allow generate additional constrictions on security parameters in hash functions which are under development now.